THE CORRELATION BETWEEN VOACABULARY MASTERY AND READING COMPREHENSION ACHIEVEMENT - Latifatul Hidayati (Premise: Journal of English Education and Applied Linguistics, 2012)
Abstract: Reading is one of the four skills in Senior High School. Instructing reading is a challenge to the teacher because it is such a complex process. Reading is not a general ability but a composition of many specific abilities. It is therefore necessary to break down general comprehension into specific skills that constitute it. The purpose of reading comprehension is to get information upon a reading text. Reading also means to comprehend the meaning from words that already known in order to increase vocabulary. But as the matter of fact, many students face difficulty in comprehending English text and the students still have difficulty in memorizing vocabulary. Furthermore, to understand English reading text the students have to have a good command of vocabulary, each word students add to their vocabularies make them a better reader. The objectives of this research are to describe vocabulary mastery and the reading comprehension achievement and to describe the correlation between vocabulary mastery and reading comprehension achievement. The subject of this research is 32 students of class X3 SMA Muhammadiyah 1 Metro. The result of this research shows that there is positive and significant correlation between vocabulary mastery and reading comprehension achievement. It is proven by the value of correlation coefficient (0.818) which is higher than the value of r –table (0.349). It means that the rise of the students’ vocabulary mastery will be followed by the rise of reading comprehension achievement.